The Cultural Significance and Cognitive Impact of National and Action Games in Uzbek and Karakalpak Societies (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This scientific article delves into the cultural significance and cognitive impact of national and action games in the societies of Uzbek and Karakalpak. These games, deeply rooted in the historical and cultural context of these regions, serve as powerful tools for cultural preservation and identity reinforcement. Furthermore, they contribute to the cognitive development of individuals by enhancing various cognitive skills such as strategic thinking, decision-making, and motor coordination. By exploring the unique characteristics of these games and their effects on both cultural and cognitive dimensions, this article sheds light on their integral role in the fabric of Uzbek and Karakalpak societies.